Institutional Processes of School Improvement from a Narrative Point of View - Murillo Estepa, Paulino; Altopiedi, Mariana (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2006)
This article presents a number of arguments and reflections on research that uses a narrative approach to understanding educational organizations. From a narrative point of view, meanings are organized in a narrative form that guarantees the understanding of phenomena that take place in every relationship system. This approach attempts to put in relation the actors’ narratives with those constructed by researchers, with the purpose of understanding the studied phenomena. In order to illustrate the adopted perspective, we describe a study of the processes developed by educational organizations that are employed in school improvement projects in Seville, Spain. Adopting the premise that the combination of different instruments for collecting information allows researchers to capture the polyphony of organizational discourses, data were collected using questionnaires and interviews. The results obtained allowed us to identify factors affecting the possibilities of introducing modifications in schools: a) those narratives that every organization constructs about itself and its teachers, and their relationships with social discourses; b) the image of those new initiatives and their congruence with original projects.URN: urn:nbn:de:0114-fqs0604141